Innovation performance, market orientation, technology orientation and firm performance in northwestern Nigeria: The role of business environment - Naala, Mohammad Nura Ibrahim. author (School of Business Innovation & Technopreneurship, 2018)
The present study focuses on the SMEs in Northwestern Nigeria, with a view to investigating the impact of innovation performance, market orientation, technology orientation, and firm performance in the northwestern part of Nigeria with moderating role of business environment. Even though there are significant interest and attention on these topics, a little empirical study that links the outcome of the variables under study in SMEs as the majority of prior research has mostly centered on large organizations. Hence, innovation performance, market orientation, and technology orientation are the independent variables of the study, while firm performance is the dependent variable. Similarly, the study focuses on the moderation of business environment on the relationship between innovation performance, market orientation and technology orientation and the performance of SMEs in Nigeria.